Pengaruh Manajemen Fasilitas terhadap Kepuasan Penghuni pada Hunian Kos Pondok Raja Living Space di Kota Semarang - Trisno Trisno; Yuniarti Rahmat Satato; Syamsul Hadi; Henry Yuliamir (OPTIMAL Jurnal Ekonomi dan Manajemen, 2026)
This study analyzes the influence of facility management on resident satisfaction in Pondok Raja Living Space, a small-scale rental residential unit in Semarang characterized by shared facilities and limited space. This study seeks to fill the literature gap that generally focuses on large-scale residential or commercial buildings by presenting empirical evidence from the context of boarding houses. Primary data was obtained through a Likert-scale questionnaire filled out by 16 out of 20 active residents, covering seven dimensions of the facility: room condition, basic furnishings, cleanliness, water availability, lighting and ventilation, electricity and Wi-Fi quality, and security. Quantitative analysis includes descriptive statistics, Cronbach’s alpha reliability test, Spearman correlation, and simple linear regression. Results showed a high average facility index (mean = 4.35) with strong internal consistency, while basic furniture obtained the lowest score (mean = 3.63) as a repair priority. The significant correlation between facility quality and occupant satisfaction confirms the central role of facility management in shaping the life experience. Regression shows a large contribution of facility quality to satisfaction variance, in line with the principles of Post-Occupancy Evaluation (POE) and the facility management literature. The study recommends improved furniture, better ventilation strategies, as well as the implementation of preventive maintenance to improve efficiency and well-being of residents. These findings provide practical guidance for local housing operators in improving the quality of small-scale residential services in Indonesia.